Peripartum Hysterectomy in a Teaching Hospital in India - Agrawal, Swati; Yadav, Reena; Raghunandan, Chitra; Dhingra, Shilpa; Kaur, Harvinder (Asian Journal of Medical Sciences, 2013)
Objectives: To find the incidence and clinical implications of peripartum hysterectomy in a tertiary care centre of India. Methods: A retrospective study of all cases of caesarean and postpartum hysterectomy between January 2006 and December 2011. Maternal characteristics, method of delivery, indications for hysterectomy and complications were reviewed. Results: The rate of peripartum hysterectomy was 0.47:1000 deliveries. Most were operative deliveries. The main indications were placenta accreta (38.88%), massive atonic PPH (36.11%) and uterine rupture (22.22%). Half the hysterectomies were subtotal while the rest were total. Maternal morbidity was high and there were seven maternal deaths (19.44%). All deaths were in patients brought in a critical condition to the hospital after massive blood loss. Conclusion: Peripartum hysterectomy is potentially a life saving procedure but the mortality and morbidity is high, especially if performed late when the hemodynamic instability has already set in. DOI: http://dx.doi.org/10.3126/ajms.v4i1.6967 Asian Journal of Medical Sciences 4(2013) 5-9